Implementasi Pendidikan Karakter Religius dan Disiplin Dalam Pembelajaran PKN KELAS V di SDIT El-Ma’mur Bogor - Latifah Hanani Harahap; Muhammad Fahri; Sutisna Sutisna (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2022)
The purpose of this research is to describe the implementation of PKN learning in shaping the religious character and discipline of students at SDITA eL Ma'mur Bogor. The method in this research is qualitatively desktiptif with the type of field study approach (Field Riserch) and research conducted in class V takes 2 classes with a total number of 61 students. Data collection techniques in this study are carried out by interview, observation and documentation. The results showed that PKN learning can shape students' character values such as religious characters and disciplines not only in theory but students can also implement them in everyday life. With the passage of several character-based school programs (Adab month) it can also be used as a reinforcement for the formation of religious character and student discipline. Keywords: Character education, Religious, Discipline, Civic Education